Efficiency, Equity, and Generalized Lorenz Dominance - Christian Kleiber; Walter Kraemer (Center for Economic Studies and ifo Institute (CESifo), 2000)
We decompose the generalized Lorenz order into a size and a distribution component. The former is represented by stochastic dominance, the latter by the standard Lorenz order. We show that it is always possible, given generalized Lorenz dominance between two distributions F and G, to find distributions H1 and H2 such that F stochastically dominates H1 and H1 Lorenz-dominates G, and such that F Lorenz-dominates H2 and H2 stochastically dominates G. We also show that generalized Lorenz dominance is characterized by this property and discuss the implications of these results for choice under risk.
Keywords: 330; Income distribution; welfare dominance; Lorenz order; stochastic dominance; decisions under risk